Application of tomato SlNF-YC9 gene and encoding protein thereof in regulating drought tolerance of tomato - LIANG YUNFEI; ZHAN XIANGQIANG; MA FANG; SUN GUOTAO; CAI YIYONG (2025)
The invention relates to the technical field of biology, and particularly provides application of a tomato SlNF-YC9 gene with a nucleotide sequence as shown in SEQ ID NO: 1, a tomato SlNF-YC9 protein with an amino acid sequence as shown in SEQ ID NO: 2 or a biological material containing the tomato SlNF-YC9 gene with the nucleotide sequence as shown in SEQ ID NO: 1 in regulation and control of tomato drought tolerance or cultivation of drought-tolerant tomatoes. And a new gene resource is provided for improvement of drought-resistant varieties of tomatoes. 本发明涉及生物技术领域，具体本发明提供了核苷酸序列如SEQ ID NO:1所示的番茄SlNF-YC9基因、氨基酸序列如SEQ ID NO:2所示的番茄SlNF-YC9蛋白或者含有核苷酸序列如SEQ ID NO:1所示的番茄SlNF-YC9基因的生物材料在调控番茄耐旱性或培育耐旱番茄中的应用，为番茄耐旱品种改良提供了新的基因资源。